Chequered Pasts : Sports Car Racing and Rallying in Canada, 1951-1991. - Charters, David (University of Toronto Press, 2007)
Based on extensive research into the CASC's records and dozens of interviews with former competitors and officials, The Chequered Past opens a window into the rich but virtually unknown history of the auto sport, and claims for it a place in Canadian sports history.